2020
DOI: 10.3390/molecules26010145
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath and Oxygenator Sweep Gas Propionaldehyde in Acute Respiratory Distress Syndrome

Abstract: Background: Oxidative stress-induced lipid peroxidation (LPO) due to neutrophil-derived reactive oxygen species plays a key role in the early stage of the acute respiratory distress syndrome (ARDS). Monitoring of oxidative stress in this patient population is of great interest, and, ideally, this can be done noninvasively. Recently, propionaldehyde, a volatile chemical compound (VOC) released during LPO, was identified in the breath of lung transplant recipients as a marker of oxidative stress. The aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“… 19 , 20 In severe cases, intraoperative oxygen desaturation can threaten the safety of patients. 21 , 22 Therefore, it is of great clinical value to prevent intraoperative hypoxemia during painless gastroscopy in patients with obesity. Our data showed no significant difference in BMI between the two groups, which indicates that the risk of respiratory depression was similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 In severe cases, intraoperative oxygen desaturation can threaten the safety of patients. 21 , 22 Therefore, it is of great clinical value to prevent intraoperative hypoxemia during painless gastroscopy in patients with obesity. Our data showed no significant difference in BMI between the two groups, which indicates that the risk of respiratory depression was similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…As a terminal product of fatty acid β-oxidation, increased 3-hydroxybutyrate typically reflects fat utilization as an energy source to compensate for the increased ketone body energetic demands following tissue damage[ 34 ]. Breath acetone is a marker of ischemia–reperfusion-induced oxidative stress, which causes lipid peroxidation and plays a key role in the early stage of ARDS[ 35 ]. A recent study showed that acetoacetate, 3-hydroxybutyric acid, and acetone were markedly elevated in the serum of patients with coronavirus disease[ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a terminal product of fatty acid β-oxidation, increased 3-hydroxybutyrate typically re ects fat utilization as an energy source to compensate for the increased ketone body energetic demands following tissue damage [19]. Breath acetone is a marker of ischemia-reperfusion-induced oxidative stress, which causes lipid peroxidation and plays a key role in the early stage of ARDS [33]. A recent study showed that acetoacetate, 3-hydroxybutyric acid, and acetone were markedly elevated in the serum of patients with COVID-19 [34].…”
Section: Discussionmentioning
confidence: 99%